2016
DOI: 10.1097/sla.0000000000001009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hospital Volume on Circumferential Resection Margin Involvement

Abstract: The outcomes of this pooled analysis support minimal volume standards in rectal cancer surgery. Low hospital volume was independently associated with a higher risk of CRM involvement (OR = 1.54; 95% CI: 1.12-2.11).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…• The controversy around institutional volume of cases is not settled. However, there is evidence to indicate that concentrated skills and expertise play a pivotal role in short and long-term surgical and oncological outcomes in the management of patients with rectal cancer [23][24][25]. TaTME should only be performed at centers with expertise in "complex" rectal cancer surgery as per CPAC guidelines [22]…”
Section: Settingmentioning
confidence: 99%
“…• The controversy around institutional volume of cases is not settled. However, there is evidence to indicate that concentrated skills and expertise play a pivotal role in short and long-term surgical and oncological outcomes in the management of patients with rectal cancer [23][24][25]. TaTME should only be performed at centers with expertise in "complex" rectal cancer surgery as per CPAC guidelines [22]…”
Section: Settingmentioning
confidence: 99%
“…In contrast to the present findings, an independent association of CRM positivity and hospital volume was documented in a study including more than 5000 rectal cancer patients undergoing primary resection in 2011–2012. A 1.5-fold higher risk of CRM involvement was observed in low-volume hospitals 30 . Another Dutch study with data from 2008 to 2013 collected from 10 community hospitals in the Southern Netherlands did not, however, show significantly higher CRM involvement in hospitals performing 20 or fewer rectal cancer surgeries per year (low-volume) compared with hospitals executing at least 40 per year (high-volume) 31 .…”
Section: Discussionmentioning
confidence: 91%
“…A total of 3012 studies were examined, and 23 comprising 293,159 minimally invasive oncologic surgeries met the inclusion criteria and were used for the descriptive analysis [ 4 , 5 , 6 , 7 , 8 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The study selection schema is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 23 studies, gastrointestinal surgery was the most common surgery type (nine studies) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], followed by genitourinary (seven studies) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ], gynecologic (four studies) [ 4 , 5 , 6 , 7 ], hepatobiliary (two studies) [ 8 , 29 ], and thoracic (one study) surgeries [ 37 ]. In the gynecologic surgery group, two studies reported the outcomes of minimally invasive hysterectomy in endometrial cancer [ 4 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation